2014
DOI: 10.1177/2158244014554204
|View full text |Cite
|
Sign up to set email alerts
|

Talking Circles for Adolescent Girls in an Urban High School

Abstract: Restorative Practices (RP) in schools is a new and emerging field. Meeting in Circles to build friendships, develop emotional literacy skills, resolve conflict, or learn interactively are some of the core components of these programs. This article describes a 2-year study of 12 weekly Talking Circles organized under the auspices of a RP program in an urban high school with 60 adolescent girls. Primary data sources included 257 hr of participant observations in Talking Circles and individual, semi-structured in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 18 publications
2
15
1
Order By: Relevance
“…The findings of this study indicated that some of the circle keepers did not maintain the integrity of the circle process and provide mature steady support to the girls. This is in contrast to previous research (Schumacher, 2014).…”
Section: The Circle Keepercontrasting
confidence: 99%
See 4 more Smart Citations
“…The findings of this study indicated that some of the circle keepers did not maintain the integrity of the circle process and provide mature steady support to the girls. This is in contrast to previous research (Schumacher, 2014).…”
Section: The Circle Keepercontrasting
confidence: 99%
“…All five informants revealed talking circles were perceived as safe collaborative spaces to encourage peer relationships. This is consistent with extant research on RP talking circles (Schumacher, 2014).…”
Section: Single-gender Talking Circlessupporting
confidence: 90%
See 3 more Smart Citations